Pengaruh Return On Equity, Debt to Equity Ratio, Debt to Equity Ratio, Earning Per Share Terhadap Harga Saham - Nona Jane Onoyi; One Yantri; Diana Titik Windayati; Nona Jane Onoyi (JURNAL MANAJEMEN, ORGANISASI DAN BISNIS (JMOB), 2021)
This research aims to determine the effect of Return On Equity, Debt to Equity Ratio, Net Profit Margin, Earning Per Share on Stock Prices in LQ45 companies listed on the Indonesia Stock Exchange for the 2016-2019 period. The research method uses a quantitative approach. The data used in this research is secondary data. The sample selectionis done by purpose sampling obtained 31 samples of companies. The results showed that partially ROE and EPS variables had a significant effect on stock prices. While the DER and NPM variables partially have no significant effect on stock prices. Simultaneously ROE, DER, NPM and EPS variables have a significant effect on stock prices.